Use of Nanosecond Laser Annealing for Thermally Stable Ni(GeSn) Alloys - Andrea Quintero; Pablo Acosta Alba; Jean-Michel Hartmann; David Cooper; Patrice Gergaud; Vincent Reboud; Philippe Rodriguez (IEEE Journal of the Electron Devices Society, 2023)
In this study, we have conclusively used UV-nanosecond laser annealing (UV-NLA) as an alternative to classical rapid thermal annealing (RTA) for the formation of stable Ni-GeSn alloys. The phase formation sequence was similar to the one obtained with RTA. At low laser energy densities (ED) and after the consumption of Ni, the Ni-rich phase, Ni5(GeSn)3, was first obtained. This phase was followed, for higher ED, by the mono-stanogermanide phase Ni(GeSn). Surface wrinkles appeared at high ED, resulting in a sheet resistance ( $\text{R}_{\text {sh}}$ ) increase. Meanwhile, $\text{R}_{\text {sh}}$ variations were mainly governed by the phases that were present at lower ED. By combining various analyses, we did not see any Ni(GeSn) agglomeration or Sn segregation. The use of UV-NLA yielded thermally stable Ni(GeSn) contact layers.